(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The paper deals with “Role of Aarogya Setu Application to Machine Learning Approach on Covid-19.” A random sample 250 male groups of the age range 25-40 and 41-65 years age has been selected from Ministry of India & Arogya Setu application. The different age groups 25-40 and 41-65 years old do not differ in terms of Aarogya Setu application. shows that 25-40 and 41-65 years age groups do not differ in terms of Aarogya Setu application. The age groups of 25-40 has been found 95.20% awareness and 41-65 years age groups was found 75.20 on Aarogya Setu application and creating awareness of various causes impacts on Covid-19.